Impact of smoking cigarette on the mRNA expression of cytokines in mucosa of inflammatory bowel disease - Vrablicova, Z; Soltys, K; Krajcovicova, A; Stuchlikova, K; Sturdik, I; Koller, T; Huorka, M; Payer, J; Killinger, Z; Jackuliak, P; Tkacik, M; Stuchlik, S; et al. (Physiological research, 2019)
It is well known that smoking is the risk factor in the development and clinical course of Crohn s disease (CD), but on the other hand, smoking is a protective factor against ulcerative colitis (UC). The pathways that are influenced by smoking in CD and UC are poorly understood. The aim of our study was to analyse the influence of smoking on the mRNA expression of cytokines in mucosa in patients with CD and UC. We performed a cross-sectional study. The cohort consisted of 86 IBD patients (48 CD patients and 38 UC patients) and took place at the IBD Centre at the University Hospital Bratislava-Ružinov. We took the demographic and clinical data of each patient, including information about their smoking habits. We performed a colonoscopy on each patient and took biopsies from both inflamed and non-inflamed sigma (CD, UC) and terminal ileum (CD). mRNA was extracted from mucosal biopsy samples for each cytokine and was normalized to a housekeeping gene (GAPDH). Finally, we compared the mRNA expression of target cytokines in the mucosa of smokers and non-smokers in IBD patients. Smokers with Crohn s disease have a significantly higher mRNA expression of pro-inflammatory cytokine TNF ? (p=0.003) in inflamed mucosa in sigma compared with non-smokers. In smokers with ulcerative colitis, we observed significantly higher mRNA expression of anti-inflammatory cytokine IL 10 (p=0.022) in non-inflamed mucosa of sigma. Similarly, smokers with UC have a significantly decreased mRNA expression of cytokine TLR 2 (p=0.024) and CCR1 (p=0.049) in non-inflamed mucosa of sigma. Based on our results, smoking has a positive influence on cessation and the clinical course of UC due to the stimulation of anti-inflammatory cytokine IL 10 in mucosa. On the other hand, smokers with CD have a higher expression of pro-inflammatory cytokine TNF ?, which could be associated with a worsening of the disease and response to therapy.
Keywords: Tobacco Smoking; kouření tabáku; Humans; messenger RNA; lidé středního věku; Colitis, Ulcerative; ulcerózní kolitida; cytokiny; Female; střevní sliznice; mladý dospělý; dospělí; Aged; Crohn Disease; senioři; lidé; Adult; RNA, Messenger; ženské pohlaví; Male; Middle Aged; Cytokines; Crohnova nemoc; Cross-Sectional Studies; Young Adult; mužské pohlaví; Intestinal Mucosa; průřezové studie